Effect of graphene oxide on the corrosion resistance and electromagnetic propertiese of FeSiAl alloy powders - GUO Yang; HU Li-ming (Fenmo yejin jishu)
To improve the corrosion resistance of the FeSiAl (FSA) alloys in the salt spray environment, the para-aminobenzoic acid (PABA) and graphene oxide (GO) were sequentially grafted and coated on the surface of the FeSiAl alloy powders to form the FSA/PABA/GO composites. The influence of graphene oxide on the corrosion resistance and electromagnetic properties of the FeSiAl alloy powders was investigated by the vector network analyzer. The results show that, the graphene oxide is uniformly coated on the surface of the FeSiAl alloy powders and tightly combined with the powders. The graphene oxide makes the corrosion potential of the FeSiAl alloys move from −0.15 to 0.08 V, and the corrosion rate is reduced from 1.21×10−11 to 4.75×10−13 m·s−1, which significantly enhances the corrosion resistance of the FeSiAl alloys in the salt spray environment. Compared with the pure FeSiAl alloys, the graphene oxide with higher conductivity significantly increases the matrix permittivity. In addition, the FSA/PABA/GO composites show the lower permeability at 0.5～10.0 GHz. The higher permittivity and lower permeability make the FSA/PABA/GO composites exhibit the poor microwave absorption performance.